Water Quality Assessment in some selected communities along the Volta River - Brown, Sheriff Enti-; Tulasi, Delali; Ackah, Michael; Anim,, Alfred Kwablah; Zakaria, Nafisatu; Osei, Juliet; Nyarko, Esther Saah; Gyamfi,, Eva Tabuaa (IJRDO-Journal of Applied Science, 2016)
Surface water samples and sediments from seven contact sites at the Volta River where small,large and domestic activities discharge their wastes were sampled. Levels of heavy metals in thesamples were determined using flame atomic absorption spectrometry (FAAS). The sedimentssamples in the study area were moderately enriched with manganese while exhibiting minorenrichment with copper, zinc, nickel and arsenic. The geo-accumulation index showed that thestudy sites were currently practically unpolluted. In the long term, the situation might change.